Design and Evaluation of the Effectiveness of the Writing Workshop on Promoting the Research Skills of Basic and Clinical Students based on Kirkpatrick's Model - Ensieh Lotfali; Hossein Tayebi; Zohre Khoshgoftar (Strides in Development of Medical Education, 2023)
Background: An increasing number of workshops are held yearly to educate medical students on academic writing and research methodology. However, the actual impact of such training programs on students’ proficiency in academic research cannot be assessed without thorough evaluation.Objectives: Herein, Kirkpatrick’s model was adopted to evaluate the efficiency of a workshop held for medical students on research methodology.Methods: This cross-sectional study collected data from 280 medical students participating in seven workshops. Herein, two levels from Kirkpatrick’s model were evaluated (reaction and learning). A 12-item questionnaire was filled out by participants immediately after the workshop to assess their reactions. Two questionnaires were used before and after the workshop to evaluate learning, each consisting of 25 items.Results: Concerning the first level of Kirkpatrick’s model, all students showed a generally high level of satisfaction in terms of the content, the lecturer, and the organization of the workshop. As for the learning scores, both basic and clinical students demonstrated significant (P<0.001) improvement within groups. However, there was no significant difference between the two groups (basic and clinical).Conclusion: The high level of satisfaction experienced by the participants and their significantly improved knowledge of research methodology, suggest that such workshops can indeed put medical students on the right track toward a productive academic and clinical career. So, the workshops should be considered a necessary component of education in medical sciences.